Breast‐feeding and human immunodeficiency virus infection: Assessment of knowledge among clinicians in Kenya. Issue 1 (21st November 2013) - Murila, Florence; Obimbo, Moses M; Musoke, Rachel; Tsikhutsu, Isaac; Migiro, Santau; Ogeng'o, Julius
<x xml:space="preserve">Abstract</x> In Kenya, human immunodeficiency virus (HIV) prevalence ranks among the highest in the world. Approximately 60 000 infections yearly are attributed to vertical transmission including the process of labour and breast‐feeding. The vast of the population affected is in the developing world. Clinical officers and nurses play an important role in provision of primary health care to antenatal and postnatal mothers. There are a few studies that have explored the clinicians' knowledge on breast‐feeding in the face of HIV and in relation to vertical transmission this being a vital component in prevention of maternal‐to‐child transmission. The aim of this study was to evaluate clinicians' knowledge on HIV in relation to breast‐feeding in Kenya. A cross‐sectional survey was conducted to assess knowledge of 161 clinical officers and nurses serving in the maternity and children' wards in various hospitals in Kenya. The participants were derived from all district and provincial referral facilities in Kenya. A preformatted questionnaire containing a series of questions on HIV and breast‐feeding was administered to clinicians who were then scored and analyzed. All the 161 participants responded. Majority of clinicians (92%) were knowledgeable regarding prevention of mother‐to‐child transmission. Regarding HIV and breast‐feeding, 49.7% thought expressed breast milk from HIV‐positive mothers should be heated before being given. Majority (78.3%) thought breast milk should be given regardless of availability of alternatives. According to 74.5% of the participants, exclusive breast‐feeding increased chances of HIV transmission. Two‐thirds (66.5%) would recommend breast‐feeding for mothers who do not know their HIV status (66.5%). This study observes that a majority of the clinicians have inadequate knowledge on breast‐feeding in the face of HIV. There is need to promote training programmes on breast‐feeding and transmission of HIV from mother to child. This can be done as in‐service training, continuous medical education and as part of the formal training within medical institutions.